Cистематизація підходів до управління виробничими відходами на поліграфічному підприємстві «УКРПОЛ» - Нерода, Т. В.; Сторожук, Д. (ТОВ «Видавництво Ліра-К», 2025)
The waste management process at a printing company was studied. The waste management system at the «Publishing House « Ukrpol» was analyzed. The use of intelligent smart containers for waste collection and monitoring was considered.
Keywords: поліграфія; управління виробничими відходами